2009
DOI: 10.1111/j.1468-1331.2009.02656.x
|View full text |Cite
|
Sign up to set email alerts
|

Bias in request for medical care and impact on outcome during office and non‐office hours in stroke patients

Abstract: Considering the fact that stroke patients admitted during non-office hours were in more severe clinical condition we found no differences in outcome. Fear of impaired access to sophisticated treatment options during non-office hours could be dispelled by the fact, that rate of thrombolytic treatment was even higher during night and weekend. Therefore, our data do not confirm a weekend effect or night effect on stroke treatment. Delay in request of medical care of mildly affected patients that suffer from strok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
33
1
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 10 publications
5
33
1
3
Order By: Relevance
“…Similar to our findings, Jauss et al 24 found no difference in short-term mortality after adjusting for clinical condition (Modified Rankin Scale at admission, disturbance of conscience, presence of motor deficits, dysarthria, aphasia, and swallowing-disorder), which was found to be more severe among the patients admitted during off-hours. Other studies have not found differences in short-term mortality when restricting to patients admitted to specialized stroke centers, indicating that organizational factors [25][26][27][28] may be important in understanding the weekend-or off-hours effect.…”
Section: Days Case-fatalitysupporting
confidence: 79%
“…Similar to our findings, Jauss et al 24 found no difference in short-term mortality after adjusting for clinical condition (Modified Rankin Scale at admission, disturbance of conscience, presence of motor deficits, dysarthria, aphasia, and swallowing-disorder), which was found to be more severe among the patients admitted during off-hours. Other studies have not found differences in short-term mortality when restricting to patients admitted to specialized stroke centers, indicating that organizational factors [25][26][27][28] may be important in understanding the weekend-or off-hours effect.…”
Section: Days Case-fatalitysupporting
confidence: 79%
“…Four year-data of 37 396 patients with stroke (2003 to 2006), from a prospective, hospital-based stroke registry for the federal state Hesse, Germany, demonstrated that patients admitted during nonoffice hours (weekend or nighttime) did not have different outcome or mortality than patients admitted during office hours after adjustment for clinical state and admission latency. 7 Nonoffice hour patients, however, were more likely to receive thrombolytics. This is similar to the findings in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…5 In the United Kingdom, weekend patients with stroke are less likely to receive thrombolytics, 6 whereas in Germany, they are more likely. 7 Studies of the stroke "weekend effect" in the United States, however, have been inconsistent. In the Get With the Guidelines-Stroke Program, off-hour ischemic stroke presentation (weekends and weeknights) is associated with slightly higher in-hospital mortality.…”
mentioning
confidence: 99%
“…14 However, a German study found no weekend effect on early stroke mortality. 15 Stroke care organization and delivery may be different in the United States than abroad. An analysis of the Get With The Guidelines-Stroke Program found a small but significant increase in in-hospital mortality for "off-hours" admission (5.8% versus 5.2%; PϽ0.001).…”
Section: Discussionmentioning
confidence: 99%